Energy absorption behaviour of braided basalt composite tube - Roslan, M. Nazrul; Yahya, M. Yazid; Ahmad, Z.; A.R., Azrin Hani (Taylor and Francis, 2018)
Braided composite had been proven to have a great potential as energy absorber. However, the past studies done were limited to synthetic fibre as the reinforcement composite. In this study, we focused on a natural fibre, namely basalt, as the reinforcement material. The effects of braid thickness, braid angle and braid tow density of the basalt composite tube subjected to quasi-static crushing response were investigated. Crushing failure mode had been observed in comparing those braid parametric effects. Moreover, the analysis of variance was used to analyse the main and interaction effects subjected to specific energy absorption (SEA) response for the test. Three crushing modes had been observed. The splayed and diamond shape of progressive folding were reported for the braid angles of ±30° and ±45°, respectively, and fibre micro-cracking mode effects for the ±60° braid angle. Furthermore, SEA increased with the decrease of braid angle and increase of diameter-to-thickness ratio. On the other hand, the highest braid angle demonstrated the lowest crush efficiency and poor triggering crushing progression.